Analisis Strategi Digital Content Marketing Untuk Mempertahankan Eksistensi Perusahaan Dalam Mewujudkan Keunggulan Bersaing (Studi Kasus Elbond Education Event Organizer) - Fico Abiyu Taufiq; Muhammad Ridwan Basalamah; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research is a qualitative research that aims to analyze digital content marketing strategies to maintain the company's existence in realizing competitive advantage at Elbond Education event organizer. This study took 5 informants consisting of 3 key informants and 2 supporting informants using purposive sampling and snowball sampling techniques. Methods of data collection in this study using interview techniques, observation and documentation. The analysis technique in this study uses data condensation analysis techniques to streamline data, increase effectiveness, and facilitate interpretation in processing data. The results of this study indicate that Elbond Education has successfully implemented digital content marketing as indicated by an increase in sales every month as well as an increase in followers, views, and interactions from social media users. In addition, consumer satisfaction with Elbond Education has also increased, as evidenced by the large number of consumers who are interested in various Elbond Education offers, which are then re-ordered by consumers. Digital content marketing also makes Elbond Education superior to other competing companies with indicators of the completeness of the platform on social media, the quality of the content published and the various offers provided. Keywords: Digital Content marketing, Company Existence, Competitive Advantage